Andalas Medical Robot Assistance (AMIRA) serves Covid-19 isolation patients. Issue 1 (January 2021) - Ridwan, F; Syamsuddin, S; Fathan, A; Ananta, A A; Bintang, G A; Jordan, A; Ningsih, Eka M; Fadel, M
Abstract: The world is currently alert to the spread of a virus known as the coronavirus. Corona Virus or Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a collection of viruses that can infect the human respiratory system until death. The spread of the virus is very fast and easy just by coming in contact with sufferers until it has contaminated almost all countries. For places prone to being exposed to viruses, especially in isolation rooms for Covid sufferers, the medical staff is terrified so that they are always on their toes; moreover, dozens of medical workers have died in handling patients. For this reason, innovation is needed to reduce contact between medical personnel and Covid-19 patients by replacing the duty of humans with robots so that the risk of infected medical workers decreases and avoids the level of work fatigue on the medical worker. The team from Andalas University created and designed a robot that could solve these problems. The robot was designed to perform activities carried out by nurses in serving patient's needs. This robot has the necessary features: food delivery, the patient room's smart position, protecting certain areas with disinfectants, reading the patient's body temperature, and a reminder of the patient's medication schedule anti-collision and providing other smart features which needed by the hospital. This robot is called Andalas Medical Robot Assistant or abbreviated as AMIRA.